Interreligious Dialogue as a Response to Processes of Secularization: A New Perspective on the World’s Parliament of Religions - Lehmann, Karsten (Interdisciplinary journal for religion and transformation in contemporary society, 2020)
Abstract This article proposes secularization theory as a tool to better understand the rationale of IRD -activities. To make this point, it starts with a review of present-day secularisation theories. On this basis, the article presents an analysis of the concept of the secular used in the context of the so-called ‘1893 – World’s Parliament of Religions’. In a final step, the author argues that IRD -activities have to be understood on the basis of an implicit juxtaposition of ‘the religious’ and ‘the secular’. They try to present a ‘religious voice’ as a response to a context perceived as being secular.